Biocomposite nanofiber matrices to support ECM remodeling by human dermal progenitors and enhanced wound closure - Anjum, Fraz (Sci Rep, 2017)
Cell-based therapies have recently been the focus of much research to enhance skin wound healing. An important challenge will be to develop vehicles for cell delivery that promote survival and uniform distribution of cells across the wound bed. These systems should be stiff enough to facilitate handling, whilst soft enough to limit damage to newly synthesized wound tissue and minimize patient discomfort. Herein, we developed several novel modifiable nanofibre scaffolds comprised of Poly (ε-caprolactone) (PCL) and gelatin (GE). We asked whether they could be used as a functional receptacle for adult human Skin-derived Precursor Cells (hSKPs) and how naked scaffolds impact endogenous skin wound healing. PCL and GE were electrospun in a single facile solvent to create composite scaffolds and displayed unique morphological and mechanical properties. After seeding with adult hSKPs, deposition of extracellular matrix proteins and sulphated glycosaminoglycans was found to be enhanced in composite grafts. Moreover, composite scaffolds exhibited significantly higher cell proliferation, greater cell spreading and integration within the nanofiber mats. Transplantation of acellular scaffolds into wounds revealed scaffolds exhibited improvement in dermal-epidermal thickness, axonal density and collagen deposition. These results demonstrate that PCL-based nanofiber scaffolds show promise as a cell delivery system for wound healing.